African biogeographical ancestry, atopic and non‐atopic asthma and atopy: A study in Latin American children. Issue 2 (11th December 2018) - da Silva, Thiago M.; Fiaccone, Rosemeire L.; Kehdy, Fernanda S. G.; Tarazona‐Santos, Eduardo; Rodrigues, Laura C.; Costa, Gustavo N. O.; Figueiredo, Camila A.; dos Santos, Darci N.; Feitosa, Caroline A.; Fattore, Gisel L.; Santos, Leticia M.; Alcantara‐Neves, Neuza M.; et al.
Abstract: Background: Genetic variants underlying African ancestry have been suggested be implicated in the ethnic‐racial inequalities reported for asthma and allergies. Objectives: To investigate the association between individual African ancestry and asthma symptoms, atopic and non‐atopic asthma, and atopy in children. Methods: A cross‐sectional study encompassing 1190 individuals was conducted. African biogeographic ancestry was estimated using 370 539 genome‐wide SNPs. Serum levels of specific IgE were measured, and skin prick test (SPT) performed for the most common local aeroallergens. Information on asthma symptoms was obtained by applying the International Study of Allergy and Asthma in Childhood questionnaire. The associations between the proportion of individual African ancestry and the outcomes investigated were analyzed through multivariate models adjusted for socio‐environmental variables, infections markers, and psychosocial factors. Results: Each 20% increase in the proportion of African ancestry was negatively associated with SPT reactivity (OR: 0.79, 95%CI: 0.66‐0.96) and positively associated with asthma symptoms in non‐atopic individuals (OR: 1.40, 95%CI: 1.03‐1.89). We estimated that socioeconomic status and number of infections mediated 28.4% of the effect of African ancestry on SPT reactivity, while 20.2% of the effect on non‐atopic asthma was explained by socioeconomic status and behavioral problems in children. Conclusions: The negative association observed between African ancestry and atopy is most probably explained by unobserved environmental or social factors that covariate with ancestry. For non‐atopic asthma, in turn, putative genetic variants of risk underlying African ancestry may play some role.